Dendritic cells process exogenous viral proteins and virus-like particles for class I presentation to CD8+ cytotoxic T lymphocytes. - Bachmann, M; Lutz, M; Layton, G; Harris, S; Fehr, T; Rescigno, M; Ricciardi-Castagnoli, P (1996)
Previous reports have indicated that both dendritic cells and macrophages have the ability to induce cytotoxic T lymphocyte (CTL) and T helper (Th) cell responses in vivo. Dendritic cells process exogenous antigens conventionally for presentation on major histocompatibility complex (MHC) class II molecules. However, unconventional processing of exogenous antigens in vitro for presentation on MHC class I molecules is still an open question. In this study, we report that a cloned dendritic cell line (D2SC/1) is able to present cell debris-associated exogenous viral proteins to MHC class I-restricted CTL in vitro. The dendritic cell line was very efficient in processing recombinant lymphocytic choriomeningitis virus nucleoprotein (LCMV NP) and presenting the class I-restricted epitope to CTL primed in vivo. Peritoneal macrophages could also process the recombinant LCMV NP for subsequent MHC class I presentation, but were less efficient compared to the dendritic cells. Furthermore, recombinant yeast-derived virus-like particles carrying the HIV-1 V3 loop (V3-VLP), which are protenaceous and do not contain any lipid, were also found to be efficiently processed by the dendritic cell line for presentation of the class I-restricted epitope. These results clearly indicate that viral proteins, in particulate form or associated with cell debris, are processed by dendritic cells for CTL induction.